PENGEMBANGAN E-MODUL SISTEM KOPLING PADA MATA PELAJARAN PEMELIHARAAN CHASIS UNTUK SISWA SMK - Fredi Trimanto; Samidjo Samidjo; Nurcholish Arifin Handoyono (Steam Engineering, 2023)
The aim of the research is to produce an e-module learning the clutch system in the subject of maintenance of light vehicle power transfer chassis for XI students at SMK Muhammadiyah Gamping. This research was developed using the research and development (R&D) model of 4-D by Thiagarajan Sammel. The stages used in the e-module process of the coupled coupling system are the definition stage, the design stage, the development stage, and the dissemination stage. This feasibility data collection by using a questionnaire. Material experts, media experts, and students as users participate in surveys to obtain evaluations and responses regarding the feasibility of developing E-modules. The data analysis technique used is quantitative descriptive analysis. The results of this research are e-module clutch system learning media that studies light vehicle power transmission maintenance. The results of the e-module feasibility test were categorized as very feasible, namely from media experts it was obtained 68.05% in the feasible category, material experts obtained 83.90% in the very feasible category, and the results of testing on students obtained 84.88% with a very feasible classification.